Two new genera and one new species of freshwater crabs of the subfamily Pseudothelphusinae (Decapoda: Brachyura: Pseudothelphusidae) from southwestern Mexico - Moreno-Juárez, Eric G.; Villalobos, José Luis; Álvarez, Fernando (Zootaxa, 2022)
Two new genera from the Chimalapas region in eastern Oaxaca, and from Zongolica, Veracruz, Mexico are presented. Mokayathelphusa angelsotoi n. gen., n. sp., which is described from Oaxaca, is placed in the subfamily Pseudothelphusinae due to the presence of a caudomarginal projection that ends apically in an ornamented plate. Alvarezius n. gen. is erected to accommodate A. zongolicae (Alvarez, Villalobos & Moreno, 2012) n. comb. This species was described in Pseudothelphusa, but a recent molecular phylogenetic analysis based on partial sequences of three genes (COI, 16S and H3) places this species outside the genus Pseudothelphusa and as a sister lineage to Tehuana. These results in combination with a morphological analysis support the establishment of the new genus.